A systematic review of Ebola virus disease outbreaks and an analysis of the efficacy and safety of newer drugs approved for the treatment of Ebola virus disease by the US Food and Drug Administration from 2016 to 2020 - Palanisamy Sivanandy; Pee Hui Jun; Lai Weng Man; Ng Sin Wei; Nicole Foo Kar Mun; Celestine Ang Jia Yii; Charissa Cheah Xiao Ying (Elsevier, 2022)
Background: The Ebola virus has started to infect humans from time to time since then and has led to several outbreaks. Due to urbanisation growth, invasion of forested areas, and close interaction with wildlife animals, the spread of the Ebola virus has caused the deadliest diseases to animals and humans. To date, the Ebola virus disease (EVD) claimed many lives of human beings and a greater number of cases were observed in the African region. Hence, a review was carried out to analyse the trends in EVD outbreaks, morbidity and mortality among EVD patients, efficacy and safety of drugs approved for the treatment of EVD. Method: The literature on EVD outbreaks, safety, and efficacy of EVD drugs were searched on Science Direct, PubMed, and Google Scholar using the MeSH terms such as ̈Ebola, Ebola virus disease, Outbreak, Epidemic, Safety, Efficacy, for the period of 2016-2020. In addition to that. Centers for Disease Control & Prevention (CDC), World Health Organization (WHO), US Food & Drug Administration, and UpToDate websites also searched for the latest reports, guidelines, approved drugs, etc. Results: There are only a few treatment options available for EVD to date, the most commonly used drugs for EVD are ZMapp, Inmazeb, and Ebanga. The review found that among these three drugs, ZMapp Plus is superior in the treatment of EVD with the current standard of care of 91.2%. INMAZEB when given at a 3 ml/kg IV dose reduced the mortality rate by 17% in subjects with EVD. Ebanga has shown a mortality rate of 35.1% when given a 50 mg/kg single IV dose. The most observed adverse effects were fever, tachycardia, diarrhoea, vomiting, hypotension, tachypnea, and chills. Conclusion: Overall, Inmazeb is the preferred drug of choice over ZMapp or other drugs for the treatment of EVD, and Ebanga is a choice in patients with cardiovascular complications. In addition to that, supportive care is very essential to control the mortality rate.